Analysis of The Types of Slang Language in Percy Jackson and Olympians: The Lightning - Kms. Raihan Dwi Putra; Munaja Rahma; Herman (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2026)
ABSTRACT: This study aimed to analyze the types of slang language used in the movie Percy Jackson and the Olympians: The Lightning Thief. The research employed a descriptive qualitative method and referred to Elisa Mattiello’s (2008) classification theory, which divided slang into five categories: Group and Subject Restriction, Secrecy and Privacy, Informality and Debasement, Vulgarity and Obscenity, and Time-Restriction, Ephemerality, and Localism. Data were collected from the film's dialogue and screenplay, then identified, categorized, and analyzed based on the context and usage of each slang expression. The findings showed that slang language appeared frequently throughout the film and served various communicative functions, such as building character identity, reinforcing group belonging, and reflecting cultural nuances in informal speech. Keywords: Slang Language, Percy Jackson, Movie Analysis, Linguistic Study